THE INFLUENCE OF MSMEs DEVELOPMENT ON ECONOMIC GROWTH IN NORTH LUWU REGENCY - Rahma Tasya; Hadrah Hadrah; Widyawanti Rajiman (CAPITAL: Jurnal Ekonomi dan Manajemen, 2024)
This research aims to provide a comprehensive and in-depth depiction of the influence of MSME development on economic growth in North Luwu Regency. The method used in this research is simple linear regression analysis. This research uses time series data issued by the Central Statistics Agency (BPS) and the North Luwu Regency Trade, Industry, Cooperatives and SMEs Service. Data collected in the last 10 years. The type of research applied in this research is quantitative. The results of this research are that the development of MSMEs has a significant effect on economic growth